Prospective associations between objective measures of physical activity and fat mass in 12-14 year old children: the Avon Longitudinal Study of Parents and Children (ALSPAC). (26th November 2009) - Riddoch, Chris J; Leary, Sam D; Ness, Andy R; Blair, Steven N; Deere, Kevin; Mattocks, Calum; Griffiths, Alex; Davey Smith, George; Tilling, Kate
Abstract : Objective To investigate associations between physical activity at age 12 and subsequent adiposity at age 14. Design Prospective birth cohort study with data collected between 2003 and 2007. Setting Original recruitment in 1991-2 of 14 541 pregnant women living in the former County of Avon (United Kingdom). Participants At age 12, 11 952 children were invited to attend the research clinic. Of these, 7159 attended, and 4150 (1964 boys, 2186 girls) provided sufficient data on exposure, outcome, and confounding variables. Main outcome measure Fat mass at age 14, measured by dual emission x ray absorptiometry, associated with physical activity at age 12, measured by accelerometry. Results Prospective associations of fat mass at age 14 (outcome) with physical activity at age 12 (exposure) were strong for both total activity (accelerometer counts/min) and for daily amount of moderate-vigorous physical activity (min/day). An extra 15 minutes of moderate-vigorous physical activity per day at age 12 was associated with lower fat mass at age 14 in boys (by 11.9% (95% confidence interval 9.5% to 14.3%)) and girls (by 9.8% (6.7% to 12.8%)). The proportion of physical activity due to moderate-vigorous physical activity was between 20% and 30% in boys and girls at the two ages. Conclusions Higher levels of physical activity, in particular activity of moderate to higher intensities, are prospectively associated with lower levels of fat mass in early adolescence. Interventions to raise levels of physical activity in children are likely to be important in the fight against obesity.